The impact of school environment on the performance of students of Public High Schools at Khyber Pakhtunkhwa Pakistan - Rafiq, Muhammad; Aajiz, Niaz Muhammad; Wahid, Fazl-e-; Rahman, Atta-ur; Mand, Rahat; Khan, Asadullah (Advances in Social Sciences Research Journal, 2016)
The Study explores the impact of school environment on the performance of students. The objectives of the study were to assess the existing environment of government Schools, to explore the impact of conducive school environment on the performance of students and to suggest some remedial measures for establishing conducive school climate. The study was carried out in the context of Khyber Pakhtunkhwa Pakistan. The population of the study was 374 public sector High Schools the same number of Principals and teachers were selected as sample from 6 districts of Khyber Pakhtunkhwa (Abbottabad, Charsadda, Kohat, Mardan, Nowshera and Peshawar). 1870 students were also included in the sample questionnaire as research instrument was developed for the data collection. Data analysis was handled with SPSS using algorithms for means, frequencies, averages and percentages. Overall analysis was carried out with the help of SPSS for applying various statistical process, tests and procedures. The key findings of the study were: majority schools were lacking the basic infrastructure like boundary walls, safety measure like gate and safety wire on the walls, clean drinking water, electricity, furniture and proper ventilation was missing, some suggestions were given at the end that the government should build proper boundary walls with enough height, electricity and fans may be may be provided to schools. Clean drinking water may be ensured and enough furniture may be provided to schools.